Chronic Endometritis: Potential Cause of Infertility and Obstetric and Neonatal Complications. (18th October 2015) - Kitaya, Kotaro; Matsubayashi, Hidehiko; Yamaguchi, Kohei; Nishiyama, Rie; Takaya, Yukiko; Ishikawa, Tomomoto; Yasuo, Tadahiro; Yamada, Hisao
Abstract : Chronic endometritis (CE) is a local inflammatory disease characterized by unusual plasmacyte infiltration in the endometrial stromal areas. CE has been neglected in gynecologic practice, as it is a less symptomatic benign disease that requires demanding and time‐consuming histopathologic examinations for the definite diagnosis. Recent studies, however, suggest the association of CE with infertility and obstetric and neonatal complications. In this review article, we aimed to update the knowledge on epidemiology, etiology, and pathogenesis of CE as well as discuss its clinical management from diagnosis to treatment.